Mathematical problem solving ability from student’s learning style in material Barisan class XI science 2 senior high school 1 CEPER - Santosa, Angela Dalta; Khotimah, Rita Pramujiyanti (AIP conference proceedings, 2023)
This study aims to describe mathematical problem solving abilities in terms of learning styles on material Barisan. This type of research is descriptive qualitative. The research subjects were three students of class XI Science 2 Senior High School 1 CEPER, each of whom had visual, auditory and kinesthetic learning styles. Data was collected by using the method of tests, questionnaires, and interviews. The data analysis technique uses the flow method which consists of data reduction, data presentation and conclusion drawing. The results showed that: Students with Auditory, Visual and Kinesthetic learning styles have met the indicators of identifying elements that are known and asked on all questions. 2) Students with Auditory and Visual learning styles have met the indicators of planning mathematical models and can integrate known data and knowledge in the form of mathematical models on all questions. Meanwhile, students with Kinesthetic learning style have not met the indicators of planning mathematical models in question number 4. 3) Students with Auditory learning styles have met the indicators of implementing problem solving strategies on all questions. Meanwhile, students with Visual learning styles have not met the indicators of implementing problem solving strategies in questions number 2, 3, and 4. Students with Kinesthetic learning styles have not met the indicators for implementing problem solving strategies in question number 4. 4) Students with learning styles are Auditory, Visual, and Kinesthetic have met the indicators of explaining the results of problem solving well on all questions.